Pengaruh Penerapan Teknologi Digital Terhadap Penggunaan Bilyet Giro dalam Bisnis Perdagangan - Milyatul Farihah; Kamilia Sari; Sumriyah Sumriyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
The development of digital technology has had a significant impact on the use of demand deposits in the trading business. This discussion aims to analyze the effect of the application of digital technology on the use of demand deposits in the retail industry. Several retail companies are still facing challenges related to technological infrastructure and the availability of reliable internet access. In order to optimize the use of demand deposits in the trading business with the adoption of digital technology, retail companies need to involve employees in training and developing technology skills. Attention to data protection and customer privacy is also required and the development of strategies to promote consumer acceptance of digital payment methods.